STRATEGI PENGEMBANGAN AGRIBISNIS NILAM DI DESA ONDO ONDOLU KABUPATEN BANGGAI - Hasan, Wahyudi (AgriMu, 2023)
Abstract Patschouli oil gives contribution enough big in state's stock exchange producer among other essential oils. But produce of patschouli oil in Indonesia still be limited and its(the production has not optimal. Patschouli oil is export commodity non migas.Requirement of essential oils world would coming from sapphire crop now shifts 600 - 800 tonnes/year. Most of this requirement supply Indonesian.In world essential oils marketing, Indonesia essential oils recognized to be best and masters market share around 80% - 90% is coming from sapphire. Remembers existence and market opportunity which still promising, hence agribusiness and sapphire market must be managed carefully.Purpose of research is system evaluation of marketing to expansion and of agrbisnis sapphire in the village Ondo ondolu causing can determine srategi what applied for its(the expansion is to the fore.Research is done near byly qualitative and is descriptive, Analysis applied is analysis SWOT to see strength, weakness and exploits opportunity to develop sapphire agribusiness in the village Ondo Ondolu District Batui Sub-Province Banggai.From analyst result which in getting where internal factor and eksternal stays at quadrant IV with axis 3,11 and 4,00 is burdens that sapphire agribusiness in the village Ondo ondolu District Batui mops is big for in developing. Keyword : essential oils, patchouli, agribusiness.